Chemical Tuning of Metal Nanocatalysts Interface for ORR Electrocatalysis. Issue 6 (19th January 2023) - Lenne, Quentin; Mattiuzzi, Alice; Jabin, Ivan; Hamon, Jonathan; Leroux, Yann R.; Lagrost, Corinne
Abstract: A series of surface‐functionalized gold nanocatalysts are synthesized. Through diazonium chemistry, calix[4]arene molecules are grafted at the gold surface. Sharing the same anchoring function and a common backbone, the calix[4]arene ligands possess distinct terminal chemical functions where the length, hydrophobic nature, and oxygen affinity are varied. Thanks to the versatility of the calix[4]arene platform, this paper only focuses on the molecular tuning of the solid/liquid interface through the change of the tail groups while electronic effects that are regulated by the anchoring function will be similar for all catalysts. Electrocatalytic tests demonstrate the influence of the tails group on the oxygen reduction reaction performances, including efficiency, selectivity, and durability. Beyond a pure geometric steric effect, it is shown that chemical properties of the ligands can effectively tune the interactions between the metallic catalyst and the electrolyte and reactants. Abstract : A chemical tuning of the solid/liquid interface of gold nanocatalysts is achieved thanks to the molecular versatility of a platform ligand. Irrespective of electronic effects due to grafting, the chemical properties at the electrolyte side are demonstrated to influence the oxygen reduction reaction electrocatalysis.